Growth Performance and Survival Rate of Hemibagrus nemurus with Different Density in a Recirculation System - Alfiani, Pipit Dwi; Putra, Iskandar; Pamukas, Niken Ayu (Jurnal Akuakultur SEBATIN, 2025)
Asian redtail catfish (Hemibagrus nemurus) is one type of freshwater fish that is popular in Indonesia. Baung fish is still an important food source for local communities and has significant economic value in various regions in Indonesia. This study aims to determine the Growth and Survival Performance of Asian redtail catfish with Different Stocking Densities Given Probiotic “raja ikan” in Feed in Recirculation System. This study was conducted for 56 days starting from September to November 2024 in the aquaculture technology laboratory, Faculty of Fisheries and Marine, Universitas Riau. The method used in this study was an experimental method with a Completely Randomized Design (CRD) experimental design with 4 treatment levels and 3 replications, so that 12 experimental units were required. The treatments used in this study were as follows: P1) 10 fish; P2) 15 fish; P3) 20 fish; P 4) 25 fish. The results showed that different stocking densities had a significant effect (P <0.05) on the growth performance of catfish. The best different stocking densities were found at p4) 25 tails, which produced % absolute weight, growth of 7.88 grams, absolute length of 3.90 cm, specific growth rate of 2.30%, feed utilization efficiency of 45.83%, and survival rate of 99%